2022
DOI: 10.1101/2022.07.13.22272435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An exploration of the genetics of the mutant Huntingtin (mHtt) gene in a cohort of patients with chorea from different tribes in 6 sub-Saharan African countries

Abstract: Background: Africans are underrepresented in Huntington's disease research. A European ancestor was postulated to have introduced the mutant Huntingtin (mHtt) gene to the continent, however recent work has shown the existence of a unique Huntingtin haplotype in South-Africa specific to indigenous Africans. Objective: We aimed to investigate the CAG repeats expansion in the Huntingtin (Htt) gene in a geographically diverse cohort of patients with chorea and unaffected controls from sub-Saharan Africa. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(57 reference statements)
1
0
0
Order By: Relevance
“…4A, Table S17). In agreement with current known epidemiological studies, we observed that pathogenic alleles in 11,[37][38][39][40] . Given that the initial ancestry assignments for our cohort were based on genome-wide data, we performed local ancestry analysis to check for admixture in these individuals, confirming that the expanded repeat alleles segregated on haplotypes of African and South Asian ancestry (Methods).…”
Section: Red Mutation Frequency In Different Populationssupporting
confidence: 93%
“…4A, Table S17). In agreement with current known epidemiological studies, we observed that pathogenic alleles in 11,[37][38][39][40] . Given that the initial ancestry assignments for our cohort were based on genome-wide data, we performed local ancestry analysis to check for admixture in these individuals, confirming that the expanded repeat alleles segregated on haplotypes of African and South Asian ancestry (Methods).…”
Section: Red Mutation Frequency In Different Populationssupporting
confidence: 93%